2022
DOI: 10.1108/bij-10-2021-0580
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the current state-of-the-art in lean healthcare literature from the lenses of bibliometric indicators

Abstract: PurposeLean healthcare (LHC) applies lean philosophy in the healthcare sector to promote a culture of continuous improvement through the elimination of non-value-added activities. Studies on the subject can be classified as conceptual (theoretical) or analytical (applied). Therefore, this research compares bibliometric indicators between conceptual and analytical articles on LHC.Design/methodology/approachFor data collection, the PRISMA Protocol was employed, and 488 articles published from 2009 to 2021, index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 97 publications
0
4
0
1
Order By: Relevance
“…O estudo selecionou a revisão sistemática de literatura por ser (1) uma metodologia transparente, rigorosa e replicável, (2) com etapas bem definidas, (3) que abrange critérios de inclusão e exclusão, (4) e que auxilia responder às questões de pesquisa (MOUSAVI ISFAHANI; TOURANI; SEYEDIN, 2019;SANTOS et al, 2022;TANARO et al;2019). O protocolo escolhido foi o PRISMA por possuir essas características e abrangeu as etapas identificação, seleção, elegibilidade e inclusão do Protocolo PRISMA (SANTOS et al, 2022).…”
Section: Revisão Sistemática E Protocolo Prismaunclassified
“…O estudo selecionou a revisão sistemática de literatura por ser (1) uma metodologia transparente, rigorosa e replicável, (2) com etapas bem definidas, (3) que abrange critérios de inclusão e exclusão, (4) e que auxilia responder às questões de pesquisa (MOUSAVI ISFAHANI; TOURANI; SEYEDIN, 2019;SANTOS et al, 2022;TANARO et al;2019). O protocolo escolhido foi o PRISMA por possuir essas características e abrangeu as etapas identificação, seleção, elegibilidade e inclusão do Protocolo PRISMA (SANTOS et al, 2022).…”
Section: Revisão Sistemática E Protocolo Prismaunclassified
“…The seminal study focused on linking quality and healthcare (Dahlgaard et al, 2011). Two concise literature review papers (Costa and Godinho Filho, 2016;Santos et al, 2023) have indicated that the number of lean tools helps address the problem through the best fit one. However, some devices have limited applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some devices have limited applications. Further, Santos et al (2023) concluded that the studies are more analytical than conceptual and need to focus on the theory building. Policymakers also majorly influence the healthcare industry (Gadolin, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The last two decades showed evolution concerning process integration (Kannengiesser et al, 2016). The next step of integration was at the Supply Chain level, which led to identifying Supply Chain main processes (Croxton et al, 2001), how to model a Supply Chain (Saen et al, 2016;Lehoux et al, 2016;De Meyer et al, 2016;Senna et al, 2016) and KPI concerning a Supply Chain (Coelho et al, 2009;Fang & Weng, 2010;Cai et al, 2009;Santos et al, 2022).…”
Section: Supply Chain Risk Management (Scrm)mentioning
confidence: 99%